دور المشرفين التربويين في تطوير الأداء الوظيفي للمعلمين الأوائل في ضوء نموذج الإشراف بالأهداف في مدارس محافظة مسقط - Hadidi, Ibrahim Ali Mubarak (Kulliyah of Education, International Islamic University Malaysia, 2021)
The study discusses the role of educational supervisors in developing the job performance of first teachers in Omani government schools in light of the goal supervision model at the Governorate of Muscat's schools from the perspective of first teachers, educational supervisors and first supervisors. The problem was the absence of educational supervisors' role in developing the first teachers' performance and the weakness in the application of goals' supervision in the supervisory processes. The objectives of the study are to identify the supervisors' role in developing the first teachers' job performance, and to present a proposed concept to activate the supervision role. Quantitative and qualitative methods in the form of a questionnaire and interviews were used for data collection. The study population consisted of 556 participants including 435 male and female teachers, and 121 supervisors. A questionnaire consisting of 54 items covering four areas: objectives, planning, implementation and evaluation) was distributed to the population; a total of 373 questionnaires and 108 from teachers and supervisors were returned respectively. For the interviews, four senior supervisors were interviewed to support the quantitative data. The findings revealed that (1) the role of educational supervisors in developing the first teachers' job performance in light of the goal supervision model was moderate in the view of the first teachers and also from educational supervisors' perspectives, (2) there were statistically significant differences regarding the presence of the supervisors' role according to experience and the job variables, and (3) the senior supervisors' perspectives on the supervisors' role in developing the first teachers' job performance in light of goal supervision model were estimated high in the areas of Implementation and Field Follow-up, and Evaluation, whereas the areas of Goals and Planning were estimated to be average to relatively low. The study concludes with presenting a concept of the objectives' supervision model to activate the role of supervisors in developing the first teachers' job performance.